Wireless technology applied in 3-axis filament winding machine control system using MIT app inventor - Quanjin, Ma; M. R. M., Rejab; M. S., Idris; Zhang, Bo; Merzuki, M.N.M.; Kumar, Nallapaneni Manoj (IOP Publishing, 2019)
Filament winding technique is a traditional composite fabrication process, which is generally used in filament winding machine with different axes motions. Current several filament winding machines have complicated and expensive control systems, which are used wire connection method to control. However, the main problem of filament winding machine system is that it is mostly controlled by the sophisticated systems using traditional connection method. The aim of this paper is to design a mobile software application to control the 3-axis filament winding machine with wireless connection using open-source platform. The 3-axis filament winding machine is briefly fabricated using aluminium profile for structure frame. The mobile application is designed to control several parameters such as winding angle, length and thickness. The mobile software is used to produce filament wound tubes, which is performed using Bluetooth. Bluetooth module is successfully applied to filament winding machine control system, which makes a significant contribution to winding machine control system methods.